An Orthodontic- Prosthetic Approach for a Missing Maxillary Lateral Incisor - Orlando Motohiro Tanaka; Lara Karolina Guimarães; Susiane Queiroz Basto; Caio Seiti Miyoshi; Marcio Furtado Niwa (Journal of Clinical and Diagnostic Research, 2020)
Restoring patients smile with congenitally missing maxillary lateral incisor often needs a challenging interdisciplinary treatment, which can be done either by canine substitution, single implants, or tooth-supported restorations. This case report describes the orthodontic treatment of an Angle Class I malocclusion, slightly convex lower third profile, absence of right maxillary lateral incisor, microdontia of the left lateral incisor, and prolonged retention of the right deciduous canine. The treatment was completed with good dental and functional occlusion with a third premolar implant-borne crown. After one-year of follow-up there was maintenance of good aesthetics, with gingival and periodontal health with stability.